Collaborative Governance dalam Implementasi Kebijakan Kota Layak Anak di Kota Kendari, Provinsi Sulawesi Tenggara, Indonesia - Yosia Sandi Pabia; Jun Matsunami; Leksono Subanu (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2022)
Introducing a Child-Friendly City (CFC) policy in Indonesia signals the Indonesian government's commitment to promoting children's rights. One of the main strategies used by Indonesia to implement CFC policy at the local government level is establishing a task force as a collaborative forum involving both state and non-state actors. However, many local governments failed to form task forces and engage non-state actors. In contrast, Kendari City is one of the cities in Indonesia that successfully created a task force and collaborated with non-state actors to implement the CFC policy. This study aims to describe the collaboration process of stakeholders in the CFC task force and investigate the main factors that influence the collaboration process. A qualitative method with a case study approach was used in this study. The findings indicate that the Kendari City government collaborates with non-state actors through decision-making processes, joint action, and resource-sharing mechanisms. The collaboration improved Kendari City's capacity to accommodate children's rights during the CFC policy implementation process. Also, this collaboration results in more targeted programs because the policy's beneficiaries, children, are also involved in the decision-making process. Further, the similarity of goals and programs among actors influences stakeholder participation in collaboration to implement CFC policy in Kendari City. Moreover, because the collaboration in CFC policy implementation involved children, the study discovered that facilitators play essential roles in enhancing children's participation and improving the communication process in the collaboration process.